(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Wastewater from manufacturing or chemical industries constitutes a very important source of water pollution. Industrial wastewater usually contains specific and readily identifiable chemical compounds. These include a variety of organic compounds. Many of these compounds, particularly the aromatic organic compounds are either carcinogenic or mutagenic in nature, which resist biological oxidation processes normally used by the industries for treating wastewater. These compounds are stable and persistent in nature with long-lasting adverse effects and they get dispersed over large areas before undergoing transformation into some other compounds. Many of these organic compounds are synthesized in the laboratory and even in very low concentration, they present a long term hazard as they are likely to accumulate either in food chain or in water sediment. Wet air oxidation (WAO) is the process of oxidizing organic matter in the presence of liquid water. Oxidation reactions take place in the aqueous environment where the water is an integral part of the reaction. Water provides a medium for the dissolved oxygen to react with the organics and can also react in part with the organics. The chemistry of wet oxidation involves free radical formation with oxygen derived radicals attacking the organic compounds and resulting in the formation of organic radicals. The efficiency of aqueous phase oxidation can be largely improved by the use of catalysts, either in the form of solids or as homogeneous catalysts. Catalysts, such as Cu2+ and Fe3+ in homogeneous system, their heterogeneous counterparts, or precious metal catalysts are used to enhance the effectiveness of the WAO process. In contrast to thermal oxidation, WAO does not produce any noxious gases like NOx, SO2, HC1, dioxins, furans, etc. Achieving complete mineralization of the organics through WAO process may not be always possible, since some low molecular weight oxygenated compounds (especially acetic and propionic acids as well as methanol, ethanol, and acetaldehyde), originally present in the wastewater or accumulated in the liquid-phase during the oxidation process, are resistant to further transformation to carbon dioxide.